Studi Empiris Pengaruh Kualitas Produk dan Promosi terhadap Minat Beli Konsumen Shopee di Era Digital - Rofi'ah; Endang Setyaningsih; Silvia Avira; Suryandari Sedyo Utami (Journal of Trends Economics and Accounting Research, 2025)
This study aims to examine the relationship between product quality and consumer interest in making purchases on Shopee, the influence of promotion on consumer purchase intention on Shopee, and the combined effect of product quality and promotion on consumer buying interest on the platform. The research uses a quantitative approach with data collected through surveys. The population in this study consists of Shopee users in Jakarta, with samples selected using purposive sampling. A total of 68 respondents participated through questionnaire distribution. Data analysis techniques include descriptive analysis and multiple linear regression. The results show that product quality has a positive and significant effect on purchase intention, promotion also has a positive and significant impact on purchase intention, and product quality and promotion simultaneously have a significant influence on consumer purchase intention on the Shopee marketplace.